The effects of tomato powder supplementation on performance and lipid peroxidation in quail - Şahin, Nurhan; Orhan, C.; Tuzcu, M.; Şahin, Kazım; Küçük, Ömer (Oxford Univ Press, 2008)
Recent studies have suggested a protective role for lycopene, an antioxidant carotenoid, in the prevention of stress including environmental stress. Tomatoes and tomato products are the major dietary source of lycopene. The objective of the present study was to investigate the effect of dietary tomato powder supplementation on the performance and lipid peroxidation of meat in Japanese quail (Coturnix coturnix japonica) exposed to a high ambient temperature of 34 degrees C. A total of 180 ten-day-old male quails were randomly allocated into 6 groups consisting of 10 replicates of 3 birds. Birds were kept in wire cages in a temperature-controlled room at either 22 degrees C (thermoneutral) or 34 degrees C (heat stress) for 8 h/d (0900 to 1700 h during the study). Birds were fed either a basal diet or the basal diet supplemented with 2.5 or 5.0% of tomato powder. Tomato powder supplementation linearly increased feed intake, live weight gain, and feed conversion (P = 0.01) under heat stress conditions but did not show the same effect at thermoneutral conditions (P > 0.05). Heat stress significantly increased malondialdehyde concentration and decreased vitamin concentrations in the serum, liver, and muscles of quail. Serum lycopene and vitamin C, E, and A(P = 0.01) concentrations increased linearly in birds at all groups. Malondialdehyde levels in serum, liver (P = 0.001), and muscles linearly decreased in all birds of both thermoneutral and heat stress groups as dietary tomato powder supplementation increased. The results of the study indicate that tomato powder modulates the oxidation-antioxidation system of the muscles in Japanese quail exposed to high ambient temperature.
Keywords: tomato powder; lipid peroxidation; malondialdehyde; stress; quail